If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -1 = 79 Reorder the terms: -1 + -8x = 79 Solving -1 + -8x = 79 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -8x = 79 + 1 Combine like terms: -1 + 1 = 0 0 + -8x = 79 + 1 -8x = 79 + 1 Combine like terms: 79 + 1 = 80 -8x = 80 Divide each side by '-8'. x = -10 Simplifying x = -10
| 4x+5-2x=3+x-12 | | 18-3(8x+4)=-6(4x-1) | | -7-8m=145 | | 1+32=-5(7x-7) | | -0.813+x=-1.096 | | (3x-4y)(7x-4y)= | | x+31=90 | | 4x+7(3x-13)=184 | | 19-3n=8(6n-8) | | 2x+2(3x+8)=-56 | | 4x+14=3x-1 | | x(x-3)+4x-3=8x+x(x+3) | | 2x^3-3x-2=0 | | x+31+x=5x-22 | | 2x-15=-3+5 | | 3x+4(3x-5)-10=0 | | y=5+x+4x^2 | | -15-4x=34+3x | | 7x+2y=50 | | 85-5x+70+10x=180 | | 3p+7=11+2p | | a-25=(-5) | | 42x+5=83 | | 3T-32=0 | | (xD^4+D^3)y=0 | | 4x^4+7x^2-6=0 | | x(x+1)=x^2+5 | | 6(5x-3)=36x | | 5x-(2)=2x+13 | | 1.0t+6.34t-2.12t= | | 4x-13=33 | | -21=k+9 |